Захист довкілля шляхом використання в цементах продуктів спалювання побутових відходів - Петрук, Марія; Дрималик, Андрій; Лугов’як, Вільгельм; Лефевр, Алан (Видавництво Національного університету «Львівська політехніка», 2001)
In opportunity of slag utilisation after burning the wastes of composite cement production is shown in the paper. Simultaneously, good technological performance of the cements is achieved and the problems of environment protection are solved.